2017
DOI: 10.2965/jwet.16-074
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Water Flux and Solute Movement during the Concentration Process of Hydrolysed Urine by Forward Osmosis

Abstract: Urine is rich in nutrients and can be applied as a fertilizer. The limitation on the application is the transportation cost for the farmlands. The cost estimation required 80% of the volume reduction for a feasible utilization of urine in the farmlands near urban areas. The volume reduction system by forward osmosis (FO) process was proposed to address this problem. In this study, the experiments on FO process with real and synthetic hydrolysed urine were performed to assess the FO performances, to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Several recent studies demonstrated the potential of FO as a concentration/separation process for ammonium and phosphorous recovery from source separated urine. The feasibility of urine concentration by FO was demonstrated, with up to a 5-fold concentration using a 5 M NaCl solution [ 171 ]. If phosphorous and potassium are concentrated, one main challenge is the relatively poor rejection of nitrogen especially under urea form by FO membranes (50–60%) [ 171 ].…”
Section: Applications Of Fo As Concentrating Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies demonstrated the potential of FO as a concentration/separation process for ammonium and phosphorous recovery from source separated urine. The feasibility of urine concentration by FO was demonstrated, with up to a 5-fold concentration using a 5 M NaCl solution [ 171 ]. If phosphorous and potassium are concentrated, one main challenge is the relatively poor rejection of nitrogen especially under urea form by FO membranes (50–60%) [ 171 ].…”
Section: Applications Of Fo As Concentrating Processmentioning
confidence: 99%
“…The feasibility of urine concentration by FO was demonstrated, with up to a 5-fold concentration using a 5 M NaCl solution [ 171 ]. If phosphorous and potassium are concentrated, one main challenge is the relatively poor rejection of nitrogen especially under urea form by FO membranes (50–60%) [ 171 ]. In that context, the improved rejection of nitrogen (50−80%) in hydrolysed urine was observed in comparison with the low rejection of neutral organic nitrogen (urea-N) in fresh urine [ 168 ].…”
Section: Applications Of Fo As Concentrating Processmentioning
confidence: 99%
“…Other forms of improvement of the FO process are in the membrane module development and draw solute improvement to reduce reverse solute flux. On the subject of FO, most studies have focused mainly on the concentration of FS with the aim of volume reduction for discharge or for resource recovery [ 34 , 35 , 36 , 37 , 38 ], at relatively high DS and FS flow rates (>1 L/min).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the draw solution should provide enough pressure to achieve five times the concentration of urine and be easily recovered in households. The osmotic pressure of 5 times concentrated urine is reported as 8 − 11 MPa which is higher than that of 2.5 MPa for seawater [8]. It is mentioned that high osmotic pressure can be easily generated by inorganic salts and organic compounds, although its recovery is difficult and energy-intensive.…”
Section: Introductionmentioning
confidence: 99%
“…Latest investigations proved the possibility to concentrate urine and recover a major portion of the nutrients it contains using FO [8]. However, it should be noticed that a critical aspect is the selection of appropriate draw solution to con-centrate urine at household level by FO.…”
Section: Introductionmentioning
confidence: 99%